Post-translational modifications and their implications in cancer - Dutta, Hashnu; Jain, Nishant (Frontiers in Oncology, 2023)
Post-translational modifications (PTMs) are crucial regulatory mechanisms that alter the properties of a protein by covalently attaching a modified chemical group to some of its amino acid residues. PTMs modulate essential physiological processes such as signal transduction, metabolism, protein localization, and turnover and have clinical relevance in cancer and age-related pathologies. Majority of proteins undergo post-translational modifications, irrespective of their occurrence in or after protein biosynthesis. Post-translational modifications link to amino acid termini or side chains, causing the protein backbone to get cleaved, spliced, or cyclized, to name a few. These chemical modifications expand the diversity of the proteome and regulate protein activity, structure, locations, functions, and protein-protein interactions (PPIs). This ability to modify the physical and chemical properties and functions of proteins render PTMs vital. To date, over 200 different protein modifications have been reported, owing to advanced detection technologies. Some of these modifications include phosphorylation, glycosylation, methylation, acetylation, and ubiquitination.Here, we discuss about the existing as well as some novel post-translational protein modifications, with their implications in aberrant states, which will help us better understand the modified sites in different proteins and the effect of PTMs on protein functions in core biological processes and progression in cancer.